Quantificação de carregadores em estações de recargas rápidas considerando tempos de recarga heterogêneos e múltiplos níveis de serviço - Darui, Caroline Beatriz Fucks (2025)
With the growth in the adoption of electric vehicles (EVs) around the world, concerns about charging infrastructure are also growing. In countries where electrified vehicles are more widely developed, problems with congestion at charging stations and the formation of long lines are beginning to emerge. Users consider this a concern, and experts in the field believe that developing a reliable charging infrastructure is key to the full development of EVs. Investments are then being made by the public and private sectors to develop infrastructure. Given the high costs, it is essential to develop research to assist in the planning of charging infrastructure, especially fast charging stations (FCSs) located on highways, which are considered essential for the safety of users on longer trips and for which high investments are attributed. In this sense, this paper proposes a methodology for quantifying chargers at RRSs located on highways, considering the formation of queues, minimizing the total cost, and the impacts on service levels. The study is carried out from the perspective of planning a highway charging infrastructure, considering a ten-year horizon, using growth projections. The data are compared with the aim of maximizing the use of the charging potential of the stations. The queuing theory model is used for simulation, based on real vehicle flow data on highways. The uncertainties associated with charging times, vehicle models and state of charge are considered through a charging time calculation algorithm that uses probability and stochasticity. The results demonstrate that as the number of BEVs circulating on highways increases, the waiting times in the charging queue may become impractical; however, the expansion of ERRs can be planned in such a way as to increase the use of the charging capacity.